PO 8473 Impact of ebola on sleeping sickness in coastal guinea: a retrospective analysis (2012–2017) from the guinean national control programme. (24th April 2019) - Camara, Oumou; Ilboudo, Hamidou; Camara, Mariame; Ouattara, Eric; Duvignaud, Alexandre; Leno, Amadou; Solano, Philippe; Malvy, Denis; Bucheton, Bruno; Camara, Mamadou
Abstract : Background: Coastal Guinea harbours the most active human African trypanosomiasis (HAT) foci in West Africa. The Guinean government and its partners are conducting HAT control activities to reduce the burden of this neglected tropical disease and, as set-up by WHO, to eliminate it as a public health problem by 2020. Unfortunately, control efforts were deeply impaired during the Ebola outbreak that struck the country in 2014–2015. The aim of the study was to evaluate the impact of this unprecedented outbreak on HAT screening and care activities and more generally on T. brucei gambiense transmission. Methods: A retrospective analysis of the data collected by the HAT-NCP between 2012 and 2013 (pre-Ebola period) and 2014–2015 (Ebola outbreak) has shown an interruption of active HAT screening activities and a rapid decrease of passive HAT screening activities as the Ebola outbreak was spreading. During the Ebola epidemic, HAT patients were also diagnosed in a later stage of the disease and attendance to post-treatment control visits was also severely affected. Results: Only 59 HAT patients were diagnosed and treated during the Ebola outbreak (January 2014–October 2015) as compared to 154 before the outbreak (February 2012–December 2013). This potentially large undiagnosed human reservoir of trypanosomes may have contributed to increased transmission levels. After Guinea was declared free of Ebola virus disease, screening activities (both passive and active) were progressively resumed. In 2016 and 2017, Guinea reported 107 and 140 HAT cases, respectively (almost twice as much as during the pre-Ebola period) and became the second most affected country after the Democratic Republic of the Congo. Conclusion: A major lesson taken from the Ebola outbreak is that disruption of medical care may lead to a quick HAT burst in areas of high transmission. Current HAT control measures combining screening and tsetse control interventions will help to stay on course for the elimination goal.